A retrospective cohort study for the treatment of Asian diabetic ketoacidosis: optimizing initial doses of insulin. Issue 1 (24th December 2021) - Hishida, Yoshiaki; Nakamura, Yuta; Tsukiyama, Hidekazu; Nakagawa, Tomoko; Sone, Masakatsu
Abstract : Aim: An insulin dose of 0.1 U/kg/h recommended by Western guidelines occasionally induces a precipitous decreasing blood glucose in Asian diabetic ketoacidosis (DKA). It is known that clinical factors, such as insulin sensitivity, differ between Asians and Americans/Europeans. We investigated how treatment options affect the time to DKA resolution to determine the optimal treatment for Asian DKA patients. Methods: This was a retrospective cohort study from a single institution in Japan. A total of 34 adult DKA patients were observed. Baseline characteristics and treatment‐related parameters were compared between patients whose DKA was resolved within 18 h and those in which it was not. Results: Significant differences were observed in the initial insulin dose (mean [standard deviation]: 0.053 [0.021] versus 0.031 [0.014] U/kg/h; P  = 0.003) and the baseline β‐hydroxybutyrate (7.2 [3.2] versus 9.9 [2.6] mmol/L; P  = 0.024) and HCO 3 − levels (11.2 [4.1] versus 7.7 [3.1] mmol/L; P  = 0.014). Multivariable logistic regression analysis revealed that the initial insulin dose was significantly associated with early resolution of DKA and was independent of basal conditions. Receiver operating characteristic curve analysis indicated that the optimal cut‐off point for the initial insulin dose was 0.051 U/kg/h. With an initial insulin dose of 0.051 U/kg/h or higher, early resolution of DKA was obtained in 92.9% of patients. Conclusion: An initial insulin dose of more than 0.05 U/kg/h provides an early resolution of DKA in Asian patients. Lower insulin doses significantly delay resolution. These results provide practical information for acute phase treatment of Asian DKA. Abstract : It is well known that clinical factors, such as insulin sensitivity, differ between Japanese and Caucasian diabetic patients. Our results suggest that an initial insulin dose of ~0.05 U/kg/h can provide early resolution of diabetic ketoacidosis in Asian patients, even though it is lower than the dose of 0.1 U/kg/h recommended by American/European protocols. Nevertheless, we also found that an insulin dose lower than 0.05 U/kg/h may delay the resolution of diabetic ketoacidosis, even in Asian patients.